Monocentrická kontrolovaná klinická studie se Sandimmunem Neoral u nemocných po transplantaci ledviny - Matl, I; Vítko, S; Lácha, J; Horcicková, M; Nosková, L; Símová, M; Táborský, P; Viklický, O; Hulínský, V; Lánská, V (Vnitrni lekarstvi, 1997)
The authors compared in a controlled clinical study two groups of patients after a first renal transplantation treated by triple drug immunosuppressive therapy. In a group of 31 patients the triple combination comprised Sandimmune Neoral. In the control group there were 30 patients who received Sandimmune. No differences were found between the two groups as regards the effectiveness of this treatment and the authors did not confirm a lower incidence of rejections described in patients treated with Sandimmune Neoral. They confirmed, however, a lower interindividual variability of Cy-A levels assessed specifically in patients treated with Sandimmune Neoral.
Keywords: rejekce štěpu; transplantace ledvin; Immunosuppressive Agents; lidé; Cyclosporine; Kidney Transplantation; cyklosporin; Graft Rejection; imunosupresiva; Humans